Paraglacial slope failures in the Aran valley (Central Pyrenees) - Fernandes, Marcelo (2020)
Slope failures are widespread phenomena in mid-latitude mountain environments that were glaciated during the Last Glacial Cycle. This is the case of the Aran valley, in the Upper Garonne catchment, Central Pyrenees, that included glaciers several hundred meters thick. Following postglacial warming and ice thinning, the recently deglaciated slopes were subject to intense stress readjustments - the so-called paraglacial dynamics. We have identified up to 135 major slope failures in the Aran valley, with only 10 units occurring outside the glaciated domain of the maximum ice extent of the Last Glacial. The presence of polished bedrock surfaces, till and moraine ridges next to some of these features evidence a close connection between glacial and slope processes. We have detected different types of slope failures affecting both bedrock (12 large catastrophic rock slope failures, 16 rock-slope deformation, 34 rockfalls, and 49 rockslides) and unconsolidated glacial sediments (14 slope readjustments on drift-mantled slopes). The average altitude of rock slope failures oscillates between 1551 and 1991 m, with a mean length ranging from 147 to 905 m and a width between 247 and 513 m. The affected surface is also highly variable, oscillating between 0.02 and 126.2 ha. Slope failures occur in different lithological settings, but they are most frequent in slate, lutite and limestone bedrocks. We conclude that most of the failures show a paraglacial origin, though other factors (i.e. lithology and topography) promoted slope instability.